Spillover Effects of Exchange Rates : A Study of the Renminbi - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 2012)
This paper estimates the impact of China's exchange rate changes on exports of competitor countries in third markets, which we call the "spillover effect". We use recent theory to develop an identification strategy in which competition between China and its developing country competitors in specific products and destinations plays a key role. We exploit the variation - afforded by disaggregated trade data - across exporters, importers, product, and time to estimate this spillover effect. We find robust evidence of a statistically and quantitatively significant spillover effect. Our estimates suggest that a 10 percent appreciation of China's real exchange rate boosts on average a developing country's exports of a typical 4-digit HS product category to third markets by about 1.5-2 percent. The magnitude of the spillover effect varies systematically with product characteristics as implied by theory.